Odpowiedzi

2009-12-01T19:52:29+01:00
Przypuszczam ze powinno byc: x-2/5-2y=5 (chyba źle napisałaś) a więc:
a)x-2y=5+ 2/5
x-y=3-2/6

x-2y= 5 2/5
x-y= 2 4/6

x=5 2/5 +2y
5 2/5+2y=2 4/6

x=5 2/5+2y
2y= 2 4/6-5 2/5

x=5 2/5+2y
2y= 2 20/30- 5 12/30

x=5 2/5+2y
2y= -98/30 /:2

x=5 2/5+2y
y= - 49/30

x= 5 2/5 + 2* - 49/30
y= - 49/30

x=5 12/30 +3 8/30
y= - 49/30

x= 8 2/3
y= - 49/3

b) x+ y/2-x/3=4 /*6
x- y/2 + y/3=-3/*6

6x+3y-2x=24 (skresl to 3y i -3y poniewaz sie redukuje )
6x-3y+2y=-3

4x=24/:4
6x+2y=-3

x=6
6*6+2y=-3

x=6
36+2y= -3

x=6
2y= -3-36/:2

x=6
y=-19,5



2 1 2